ANALISIS KEBIJAKAN PENDIDIKAN ISLAM INDONESIA DI ERA REFORMASI - Abdul Hayi; Mohamad Alwi (Prodi PAI STIT Sunan Giri Bima, 2023)
In national education, Islamic religious education occupies a very important position in building human capabilities, having morals, being responsible and exploring all the potential that exists in humans. As a Muslim-majority country, the issuance of National Education System Law Number 20 of 2003 was a turning point in the continuation of Islamic education in Indonesia. Three important points are contained in the 2003 National Education System Law relating to Islamic education, which include: recognition of Islamic educational institutions such as madrasas and Islamic boarding schools, recognition of Islamic education as a subject in public schools and madrasas, and recognition of Islamic education as a value in national education system. The purpose of this study is to describe and explore how educational policy is in the reform era. This study uses a qualitative method which emphasizes ''Analysis of Islamic Education Policy in the Reform Era''. While for the preparation of this study using the method of study literature in search of data sources. Data is generated from several sources, in the form of books, journals and several research results related to research discussion.